METHODS OF ASSESSMENT OF FUTURE ENGLISH LANGUAGE TEACHERS’ WRITING COMPETENCIES - Ibotova Xurshida Nasimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article provides a comprehensive review of various methods used to assess the writing competencies of future English language teachers. Recognizing the importance of effective writing skills in language education, the study aims to analyze existing literature, present different assessment methods, and discuss their implications for teacher training programs. The findings contribute to the ongoing discourse on enhancing the quality of English language education through targeted assessments of writing competencies.